Importance of spectrally invariant broadband attenuation of light in indoor photovoltaic characterization - Stefan Zeiske (APL Energy, 2023)
Indoor photovoltaic (IPV) devices are poised to make a significant contribution to the proliferation of the “Internet of Things” (IoT). For the accurate intercomparison of IPVs (and, hence, to advance the rational development of the technology), lighting conditions representative of those in typical indoor settings must be created reproducibly. As indoor lighting is invariably broadband, this will typically require the use of optical attenuation to achieve varying irradiance conditions at the device under test location. However, most forms of optical attenuation will suffer from some degree of spectral dispersion, creating sources of uncertainty for key figures of merit, such as power conversion efficiency. In this work, we examine the contribution of the mode of optical attenuation to the accurate characterization of IPV systems. We discuss requirements for broadband light source attenuation for the accurate characterization of photovoltaic devices under indoor illumination and consider the importance of using suitable reference devices for light intensity calibration. Furthermore, we experimentally verify attenuation methods typically used, including power control of the light source itself, use of neutral density filters, and advanced attenuation based on tandem prism attenuators. Finally, spectral shape alteration-induced uncertainties in performance parameter determination of photovoltaic cells under indoor illumination are quantified for three common broadband light attenuation methods, where we found ∼2%, ∼6%, and up to ∼15% ambiguity in photovoltaic device efficiency when using LED power control, prism attenuators, and neutral density filter-based broadband light attenuation, respectively.